A FUNDAMENTALS ASSET PRICING MODEL: MEASURING DIFFERENCES BETWEEN FIRMS IN THE UK MARKET - Gradwell, Matthew (2012)
In light of the financial crisis in 2007, there is an obvious issue with the current asset pricing models being used in risk assessment today. The CAPM, which is used by over 70% of firms, has a known number of anomalies and mispricing. An alternative asset pricing model which is currently under researched appears to provide many answers to the issues found in CAPM. Whereas the CAPM is based on future stock valuations and operates under a strict set of assumptions such as assuming the market is efficient, the fundamental beta assesses risk directly from historical data found in firms annual accounts. Due to the under-researched area, this essay looks to find a number of uses on the fundamental beta, looking at mostly unquoted firms in the UK. To start we estimate three risk variables which will affect return of a firm; Market return, size, and liquidity. We then proceed show that our fundamental beta is able to detect the difference between a quoted and unquoted firm, and more importantly is able to assess an unquoted firm (unlike CAPM). We also find that the fundamental measure is able to detect a difference between industries, and we finally conclude that our choice in risk variables were correct, where the three variables were able to account for over 90% of average return. One of the major limitations in this essay is that it failed to take account of the different accounting standard being used by firms. This has been highlighted to have a significant effect on returns, however it is beyond the scope of this essay to handle it.